Intra-Arterial Chemotherapy with Osmotic Blood-Brain Barrier Disruption for Aggressive Oligodendroglial tumors: Results of a Phase I Study - Guillaume, Daniel J. (2010)
OBJECTIVE: Refractory anaplastic oligodendroglioma (AO) and oligoastrocytoma (OA) tumors are challenging to treat. This trial primarily evaluated toxicity and estimated the maximum tolerated dose (MTD) of intra-arterial (IA) melphalan, IA carboplatin and intravenous (IV) etoposide phosphate in conjunction with blood-brain barrier disruption (BBBD) in these tumors. The secondary measure was efficacy. METHODS: Thirteen subjects with temozolomide (TMZ) - refractory AO (11) or OA (2) underwent BBBD with carboplatin (IA, 200 mg/m2/day), etoposide phosphate (IV, 200 mg/m2/day), and melphalan (IA, dose escalation) every 4 weeks, for up to 1 year. Subjects underwent melphalan dose escalation (4, 8, 12, 16, and 20 mg/m(2)/day) until the MTD (one level below that producing grade 4 toxicity) was determined. Toxicity and efficacy were assessed. RESULTS: Two of four subjects receiving IA melphalan at 8 mg/m(2)/day developed grade 4 thrombocytopenia, thus the melphalan MTD was 4 mg/m(2)/day. Adverse events included asymptomatic subintimal tear (1 subject) and grade 4 thrombocytopenia (3 subjects). Two subjects demonstrated complete response, 3 had partial responses, 5 demonstrated stable disease and 3 progressed. Median overall PFS was 11 months. Subjects with complete or partial response demonstrated deletion of chromosomes 1p and 19q. In the 5 subjects with stable disease, 2 demonstrated 1p and 19q deletion and 3 demonstrated 19q deletion only. CONCLUSION: In these patients with AO or OA tumors who failed TMZ, osmotic BBBD with IA carboplatin, IV etoposide phosphate, and IA melphalan (4mg/m2/day for 2 days) shows acceptable toxicity and encouraging efficacy, especially in subjects demonstrating 1p and/or 19q deletion.